DEVELOPMENT AND APPLICATION OF AN ANATOMICAL BIOMODEL FOR TEACHING ORCHIECTOMY IN DOGS - Vilela, Júlia Marcela Vasconcélos de Moraes; Bonifácio, Nadielli Pereira; Treichel, Tiago Luís Eilers; do Prado, Tales Dias (Seven Editora, 2026)
The teaching of veterinary surgery requires strategies that enable the development of technical skills in a safe and ethical manner. In this context, the present study aimed to develop an anatomical biomodel of the male canine genitourinary region for training in the orchiectomy technique, as well as to evaluate its applicability as a didactic tool. The biomodel was constructed using low-cost materials, including biscuit modeling clay for support structures, clear rubber for internal anatomical components, and platinum-cured transparent silicone to simulate the skin layer. After fabrication, the model was subjected to practical testing, in which the fundamental steps of the surgical procedure, such as incision, dissection, and manipulation of anatomical structures, were performed. The results demonstrated that the biomodel presented adequate anatomical fidelity and mechanical properties compatible with surgical simulation, allowing the procedure to be carried out in a safe and reproducible manner. From an educational perspective, the model enabled repeated practice in a controlled environment, contributing to the improvement of practical skills, reduction of errors, and increased student confidence. Furthermore, its use is aligned with the principles of reduction, refinement, and replacement (3Rs), representing an ethical alternative to the use of animals in teaching. It is concluded that the proposed biomodel has strong potential to be incorporated as a complementary tool in veterinary surgical education, contributing to the training of more qualified professionals.